Homo sovieticus or experienced worker? – what do the employers think of 50+ workers - Krzyżanowska, Łucja (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The ageing of Polish society and threat of severe crisis of pension system makes employment of the older generation of workers the key issue around. One of the many arguments against the crucial reforms of pension system is a preconception the employers will not be eager nor to employ the old people nor to keep them hi red up to their retirement. Surveys done among Polish employers show very strong negative stereotypes of the 50+ generation (people above their 50th year of life) of workers. Those stereotypes have strong impact on key decisions referring to human resources management in Polish companies as well as influencing professional life and careers of the 50+ group of workers. Among the homo sovieticus features sticked to 50+ workers there are primarily: lack of self-dependence and demands, which are considered the worst remaining of the communist system stopping smooth adaptation to capitalism. This strengthens the prejudice it is not worth to invest, educate or promote the 50+ workers. Bad health condition and lack of age management in Polish companies make the situation even worse for the workers. The campaigns undertaken did not prove successful so far and there are not enough jobs on the market for the 50+. The widespread youth cult marginalises their experience, knowledge and passionate involvement. The reform of pension system limited just to raising the retirement age up to 67 year of life, as it is planned by Polish government, may therefore prove insufficient to keep the "old people" working longer.